2019
DOI: 10.1002/eco.2089
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological function of rapidly induced biocrusts

Abstract: In dryland ecosystems, land degradation and erosion pose severe threats to ecosystem productivity and human well-being. Bio-inoculation of degraded soils with native biological soil crusts ("biocrusts") is a promising yet relatively untested means to improve soil stability and hydrological function (i.e., increase infiltration and reduce run-off). In a degraded semiarid grassland on the Colorado Plateau, we studied the establishment and hydrological function (via simulated rainfall) of induced biocrusts grown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…Wind velocities observed near the site during the growth phase were greater than average (Figure S4; USGS Clim‐met data, Urban, ), and the stabilizer may have served to anchor biocrust aggregates during development and during the experimental wind simulation. In a parallel rainfall simulation experiment (Fick et al, ), loose particles from biocrust inoculation were implicated in higher sediment yields, but this trend was ameliorated when stabilizer was added. The gelatinous nature of the stabilizer itself may have promoted the development of cyanobacterial filaments by providing interstitial ‘bridges' among coarse sand particles (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wind velocities observed near the site during the growth phase were greater than average (Figure S4; USGS Clim‐met data, Urban, ), and the stabilizer may have served to anchor biocrust aggregates during development and during the experimental wind simulation. In a parallel rainfall simulation experiment (Fick et al, ), loose particles from biocrust inoculation were implicated in higher sediment yields, but this trend was ameliorated when stabilizer was added. The gelatinous nature of the stabilizer itself may have promoted the development of cyanobacterial filaments by providing interstitial ‘bridges' among coarse sand particles (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Average windshear velocities equal to or exceeding 0.69 m s -1 , the point at which flux estimates began to significantly differ by treatment in this study, occur approximately 3% and 26% of the time for average and peak wind velocities, respectively. [Colour figure can be viewed at wileyonlinelibrary.com] simulation experiment (Fick et al, 2019), loose particles from biocrust inoculation were implicated in higher sediment yields, but this trend was ameliorated when stabilizer was added. The gelatinous nature of the stabilizer itself may have promoted the development of cyanobacterial filaments by providing interstitial 'bridges' among coarse sand particles (e.g.…”
Section: Synergistic Effects Of Biocrust Inoculation and Soil Stabilizermentioning
confidence: 99%
“…The experiment involved six treatments that comprised combinations of two amendment techniques: the application of biocrust slurry, and the application of psyllium husk powder as a soil stabilizer. Two different application rates of the slurry were used that represented one tenth and one hundredth of the biocrust found in the remnant ecosystem (these are referred to hereafter as the 1:10 and 1:100 biocrust amendments, respectively); the 1:10 amendment was comparable to rates applied in previous studies of slurry application (Fick et al, 2019(Fick et al, , 2020, while the 1:100 amendment, to our knowledge, is a novel treatment designed to test if a diluted slurry can achieve similar results to the more concentrated treatment. Each of the 90 plots were randomly assigned one of the six treatments (15 replicates of each treatment), which were as follows: (1) control (no additions of biocrust or psyllium), (2) psyllium, (3) 1:10 biocrust amendment, (4) 1:10 biocrust + psyllium, (5) 1:100 biocrust amendment, and (6) 1:100 biocrust + psyllium.…”
Section: Study Site and Experimental Designmentioning
confidence: 99%
“…Furthermore, the role of psyllium might need to be considered in the context of the spatial arrangement of arid ecosystems, which generally include run-off zones (where water runs over the surface) and run-on zones, or islands of fertility (Ludwig et al, 2005). Fick et al (2019) found that plots with psyllium amendments had greater infiltration and lower run-off than both plots with biocrust amendment only and control plots (no treatments). Such factors should be considered if the aim is to restore heterogeneous environments that resemble the remnant arid vegetation.…”
Section: Psylliummentioning
confidence: 99%
“…During the current review, an attempt was made to link between the crust properties and above all, the biocrust-induced EPS and the hydrological mechanisms responsible for runoff generation in arid and semiarid regions. While under similar environmental conditions the amount of EPS may serve as a crude indicator for the crust capability to partially clog the The role of biocrust-induced exopolymeric matrix in runoff generation in arid and semiarid zones -a mini review surface pores (Kidron et al, 2003), for a more complete and reliable outcome, evaluating the EPS properties is of major importance (Chenu, 1993;Fick et al, 2019;Kidron et al, 2020). It follows that among the important functions carried out by the EPS, EPS may play an important role in runoff generation, as in the case of NRS, which may therefore substantially impact the hydrology, geomorphology, pedology and ecology of arid and semiarid ecosystems.…”
Section: Synthesismentioning
confidence: 99%